Code of corporate governance as a catalyst to companies’ performances: A review of Malaysian experience - Ghazali, Zahiruddin; Abdul Manab, Norlida (2013)
This study aims to highlight whether the implementation of Malaysian Code of Corporate Governance in 2000 and the revise version in 2007 gives a favourable impact to Malaysian Bourse listed companies’ performances.Using a standard and reliable accounting variables with acceptable non-parametric testing methods provide justifiable research methodology.Although results were found to be in tandem with prior studies, it is found that both MCCGs fail to produce a lasting mechanism in enhancing companies’ performances.